2007
DOI: 10.1254/jphs.fp0061244
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic Mechanisms of Ananas comosus L. Leaves in Mice: Different From Fibrates but Similar to Statins

Abstract: Abstract. In this study, we investigated hypolipidemic mechanisms of the ethanolic extract of Ananas comosus L. leaves (AC) in mice and then determined its activities in related enzymes. The results showed that AC (0.40 g / kg) significantly inhibited the increase in serum triglycerides by 40% in fructose-fed mice. In mice induced by alloxan and high-fat diets, serum total cholesterol remained at a high level (180 -220 mg / dl) within 7 days of removing high-fat diets but reached normal level (120 -140 mg / dl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 14 publications
2
57
0
6
Order By: Relevance
“…The extract also inhibited the development of insulin resistance in HepG2 cells. The ethanolic extract of pineapple leaves with high phenolics has significantly inhibited the increase in serum triglycerides by 40% in fructose-fed mice (Xie et al, 2007). The extract selectively activated lipoprotein lipase coenzyme A reductase activity by 20-49% in vitro thereby indicating the hypolipidemic effect of the extract.…”
Section: Utilization Of Pineapple Wastementioning
confidence: 95%
“…The extract also inhibited the development of insulin resistance in HepG2 cells. The ethanolic extract of pineapple leaves with high phenolics has significantly inhibited the increase in serum triglycerides by 40% in fructose-fed mice (Xie et al, 2007). The extract selectively activated lipoprotein lipase coenzyme A reductase activity by 20-49% in vitro thereby indicating the hypolipidemic effect of the extract.…”
Section: Utilization Of Pineapple Wastementioning
confidence: 95%
“…Neste contexto, crescem em importância estudos para o desenvolvimento de novas alternativas terapêuticas eficazes e acessíveis às populações de baixa renda, sendo as plantas medicinais aliadas extremamente úteis, pois fornecem extratos e compostos químicos isolados, cujas capacidades anorexígena e hipolipidêmica vêm sendo demonstradas em inúmeros trabalhos científicos de várias partes do mundo (Kidwai & Upreti, 1993;Jorge et al, 1998;Heerden et al, 2007;Lei et al, 2007;Xie et al, 2007;Bahramikia & Yazdanparast, 2008;Cardozo et al, 2008;Harnafi et al, 2008;Murray et al, 2008;Ming et al, 2009).…”
Section: Introductionunclassified
“…Both HE and quercetrin lowered serum-TG levels, similar to the simvastatin group. A previous study using other plants suggested that these effects are attributed to the restoration of TG catabolism by stimulating lipolytic pathways involving plasma lipoprotein lipase (LPL) (Xie et al, 2007). Moreover, quercetin can reduce the activities and mRNA levels of several enzymes involved in the synthesis of fatty acids (Odbayar et al, 2006).…”
Section: Discussionmentioning
confidence: 99%